2004
DOI: 10.3748/wjg.v10.i16.2391
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of human intestinal capillariasis in Taiwan

Abstract: Human intestinal capillariasis is a rare parasitosis that was first recognized in the Philippines in the 1960 s. Parasitosis is a life threatening disease and has been reported from Thailand, Japan, South of Taiwan (Kaoh-Siung), Korea, Iran, Egypt, Italy and Spain. Its clinical symptoms are characterized by chronic diarrhea, abdominal pain, borborygmus, marked weight loss, protein and electrolyte loss and cachexia. Capillariasis may be fatal if early treatment is not given. We reported 14 cases living in rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…However, there was no detailed and complete investigation has yet been conducted to study the disease in Taiwan. 6 Geographically, Taiwan is the closest area to the Philippines. It is also a key rest stop on the north-south migratory routes for many fishfeeding migratory birds, which are thought to be the major carriers of Capillaria philippinensis.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no detailed and complete investigation has yet been conducted to study the disease in Taiwan. 6 Geographically, Taiwan is the closest area to the Philippines. It is also a key rest stop on the north-south migratory routes for many fishfeeding migratory birds, which are thought to be the major carriers of Capillaria philippinensis.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A diagnosis of capillariasis is based on the recovery of eggs, larvae, and/or adult worms from the stool of patients, although multiple stool samples may be required for an early diagnosis in some cases caused by the sporadic excretion of eggs in the feces. 14 However, these diagnoses are difficult in non-endemic areas, as this remains an unknown disease among many physicians and laboratory workers. 15 In addition, small intestinal aspirations or biopsies may be necessary to confirm the presence of a C. philippinensis infection.…”
Section: Introductionmentioning
confidence: 99%
“…Reports showed that the infection was endemic in the Philippines, with the appearance of few epidemics that caused deaths among infected patients (Bair et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The thick-shelled eggs mature in water and infect the small fish when it feeds on organic matter containing the mature eggs. These infected small fish are eaten raw, as they are smaller than being eviscerated; the production of thick shelled eggs and infective larvae is alternating in the same host (Bair et al, 2004;Lu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%